Formulasi dan Uji In Vivo Krim Luka Bakar dari Ekstrak Daun Alpukat (Persea americana Mill.) pada Mencit (Mus musculus) - Usman, Yusnita; Muin, Rahmatullah; Muthmainna B (BORNEO JOURNAL OF PHARMASCIENTECH, 2025)
The flavonoid content of avocado leaves (Persea americana Mill.) supports its activity in healing burns. This research aims to make a cream formula from avocado leaf extract (Persea americana Mill.) and test the activity of this preparation in vivo using mice with 1x1 cm2 burn wounds. The cream formula is made with 4 different extract concentrations, namely F0 (cream base), F1 (1%), F2 (5%), and F3 (10%). Then, the physical characteristics of the preparation are evaluated, namely organoleptic, pH, homogeneity, spreadability, adhesive power and emulsion type. Next, an activity test was carried out using 12 mice which were divided into 4 groups treated according to the cream formula that had been made with observation for 14 days. The physical characteristics test results were analyzed based on the physical condition of the cream preparation according to the test category, while the activity test results were analyzed based on the percentage of wound healing area. The results showed that the formulation was an O/W type, semi-solid, with a greenish color, consistent with the extract concentration, and all physical parameters met the requirements. Activity testing demonstrated the highest burn wound healing percentage at F4, at 76%. Therefore, it was concluded that avocado leaf extract can be formulated into a cream with good in vivo activity for healing burns in mice.